Facile strategy to construct a self-healing and biocompatible cellulose nanocomposite hydrogel via reversible acylhydrazone. (15th August 2019) - Xiao, Guifa; Wang, Ying; Zhang, Hui; Chen, Liheng; Fu, Shiyu
Graphical abstract: Highlights: Acylhydrazone bond was introduced into DACNCs-based hydrogel for the first time. DACNCs was chosen as a cross-linker and reinforcing nano-phase in hydrogel. Hydrogel possessed strength-enhanced, biocompatible and self-healing properties. Self-healing process could be easily realized under ambient circumstances. Abstract: Facile strategy to construct a cellulose nanocomposite hydrogel with self-healing and biocompatible properties is reported by crosslinking dialdehyde cellulose nanocrystals with acylhydrazine-terminated polyethylene glycol via dynamic reversible acylhydrazone for the first time. The effects of process variables on gelation time, mechanical strength and self-healing efficiency of hydrogels were investigated. It was found that gelation time shortened from hours to seconds by adjusting gelator and catalyst concentration. Tensile and compressive strength of hydrogel could reach 141 K Pa and 580 K Pa at 20.1% gelator concentration, respectively. Interestingly, the as-prepared hydrogel presented excellent self-healing ability without additional stimuli whose healing efficiency was higher than 90% even at higher gelator concentration. Furthermore, Cytotoxicity test showed that cell viability almost reached 100% after culturing with hydrogel, which revealed the hydrogel was biocompatible.